2009
DOI: 10.1007/s10800-009-9857-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of Ni-based anodes for solid oxide fuel cells

Abstract: The catalytic activity of Ni-based anodic materials was investigated in complete solid oxide fuel cells (SOFCs) by electrochemical analysis. Button cells, consisting of supporting yttria-stabilized zirconia (YSZ) electrolyte layer, (La1-xSrx)y MnO3 (LSM) cathode and (cermet) Ni0.5Co0.5–YSZ anode were employed. Powders for anodes were obtained by wet impregnation. This pro- cedure allowed easy production of composite electrodes with homogeneous distribution of phases and controlled microstructure. Two electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…As has been mentioned, a weak P H2 dependency is observed for the Ni/YSZ system in most cases. [22][23][24][39][40][41] The reaction orders' dependences upon P H2 range from −0.26 to 0.15 in different studies. Strong dependence can only be observed at very low P H2 regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been mentioned, a weak P H2 dependency is observed for the Ni/YSZ system in most cases. [22][23][24][39][40][41] The reaction orders' dependences upon P H2 range from −0.26 to 0.15 in different studies. Strong dependence can only be observed at very low P H2 regions.…”
Section: Discussionmentioning
confidence: 99%
“…Different tendencies between Ni and oxide anodes have been observed. H 2 partial pressure in most cases affects the overall performance very little for the Ni-based anodes, [22][23][24][25] but it was generally shown that the performance of oxide anodes depended heavily on it. [26][27][28] Therefore, in continuation from our previous work, 29 the reaction mechanisms and rate-limiting steps for such oxide electrodes in an anodic environment are investigated in more detail in this paper.…”
mentioning
confidence: 99%
“…For instance, attention has been paid to the formulation of lanthanum perovskites, that is LaAlO 3 , 3 for various catalytic reactions, such as oxidative methane coupling 4 and NO x ‐assisted soot combustion, 5 and as a support for transition metal catalysts 6 . In the frame of perovskite production, La plays a central role also in the development of cathodes for low‐temperature solid oxide fuel cells 7 and recently LaCoO 3 has been reported as a suitable catalyst for NO oxidation 8 . Lanthanum is reported as an important stabilizing agent for γ ‐Al 2 O 3 , 9–12 and it allows higher ethylene yield in ethanol dehydration 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] These membranes have to fulfil several requirements: (1) they have to be thin enough (o1 mm) to reduce ohmic losses to values below 0.15 O cm À2 at temperatures below 500 1C. 6,[11][12][13] (2) Full crystallinity of the metal oxide electrolytes has to be assured. Ongoing crystallization processes and amorphous residues are disadvantageous for ionic diffusion in a transforming ''metastable'' lattice.…”
Section: Introductionmentioning
confidence: 99%